Analisis Isi Pesan Dakwah Dalam Buku The Miracle of Giving Karya Yusuf Mansur - Gesit Gesit; Muhammad N. Abdurrazaq (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
In carrying out da'wah activities one can do it in various ways. One of what Yusuf Mansur did was preaching through written media. He provided motivation and inspiration about the enormity of the magic of alms and night prayers as well as sunnah services that can increase the level of prayer, as well as efforts to make it come true more quickly. Yusuf Mansur in his book The Miracle Of Giving emphasizes that worship is a solution, even a method to overcome various life problems and achieve happiness. The purpose of this study is to find out what the contents of the da'wah messages are contained in The Miracle Of Giving, and what are the contents of the dominant da'wah messages in The Miracle Of Giving. This research method is a quantitative content analysis method with a descriptive approach. The results of this study state that in the book The Miracle of Giving there are 26 messages of preaching aqidah, 35 messages of sharia preaching and 67 messages of moral preaching. The most dominant da'wah messages in The Miracle Of Giving are moral messages with a percentage of 52.34%, followed by sharia messages with a percentage of 27.34% and finally messages of faith with a percentage of 20.32%.Keywords: Analysis; Contents of Da'wah Messages; The Miracle of Giving book AbstrakDalam melakukan kegiatan dakwah seseorang bisa melakukannya dengan berbagai hal. Salah satu yang dilakukan oleh Yusuf Mansur adalah berdakwah dengan media tulisan. Beliau memberikan motivasi dan inspirasi tentang dahsyatnya keajaiban sedekah dan shalat malam serta ibadah-ibadah sunnah yang mampu meningkatkan kadar doa, juga usaha agar lebih cepat terkabulkan. Yusuf Mansur dalam Karya bukunya The Miracle Of Giving menekankan bahwa ibadah adalah sebuah solusi, bahkan metode untuk mengatasi berbagai problematika kehidupan dan mencapai kebahagiaan. Tujuan penelitian ini adalah untuk mengetahui apa isi pesan dakwah yang terkandung dalam buku The Miracle Of Giving, dan apa isi pesan dakwah yang dominan dalam buku The Miracle Of Giving. Metode penelitian ini adalah metode analisis isi kuantitatif dengan pendekatan deskriptif. Hasil penelitian ini menyatakan bahwa dalam buku The Miracle of Giving terdapat pesan dakwah akidah sebanyak 26 pesan, pesan dakwah syariah sebanyak 35 pesan dan pesan dakwah akhlak sebanyak 67 pesan. Pesan dakwah yang paling dominan pada buku The Miracle Of Giving adalah pesan akhlak dengan persentase 52,34%, yang diikuti oleh pesan syariah dengan persentase 27,34% dan terakhir pesan akidah dengan persentase 20,32%.Kata Kunci: Analisis; Isi Pesan Dakwah; Buku The Miracle of Giving